PENEGAKAN HUKUM PELAKU ILLEGAL MINING DI INDONESIA - Setiawan, Hery (Journal of Law ( Jurnal Ilmu Hukum ), 2025)
ABSTRACT. The mining law has regulated the types of violations and sanctions that can be imposed on violators. However, the reality on the ground shows that these sanctions often do not have the expected deterrent effect. Additionally, the challenges of law enforcement in cases of illegal mining also include corruption and conflicts of interest. In some areas, law enforcement officials and government officials who are supposed to take action against perpetrators are instead involved in corrupt practices, thus undermining the ongoing legal processes. This research focuses on the impacts of illegal mining in Indonesia and law enforcement against illegal mining perpetrators in Indonesia. This research uses normative research, in which normative legal research is a process to find legal rules, legal principles, and legal doctrines to address the legal issues raised, using the statutory approach and the case approach. The impacts are very detrimental in various aspects. From an environmental standpoint, this activity causes deforestation, water pollution, land degradation, and air pollution, which damage ecosystems and threaten public health. Strong and sustainable law enforcement is essential to deter illegal mining perpetrators and protect the community from its negative effects. Keywords: Law Enforcement, Illegal Mining.